The Effects of Social Status and Culture on Delay Discounting1. (25th March 2017) - Ishii, Keiko; Eisen, Charis; Hitokoto, Hidefumi
Abstract: People generally tend to discount future outcomes in favor of smaller but immediate gains (i.e., delay discounting). This study examines the hypothesis that culture and social status moderate this tendency, as well as the alternative hypothesis that social status and culture influence delay discounting independently of each other. American and Japanese adults were asked to choose receiving hypothetical monetary rewards either immediately or receiving rewards of different amounts with a delay of 1 year. The results replicated previous findings and supported the alternative hypothesis. Delay discounting was lower when subjective socioeconomic status (i.e., an individual's perception of her or his social rank) was higher. Also, the Japanese were less likely to discount future rewards than the Americans. However, there was no interaction between social status and culture in influencing the rates of delay discounting.